2006
DOI: 10.1111/j.1464-410x.2006.06380.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical treatment on nocturia in men with benign prostatic obstruction

Abstract: Several important topics are presented in this section, including the impact of surgical treatment on nocturia in men with BPH, pelvic floor exercises for stress urinary incontinence, chronic prostatitis in puberty, introital ultrasonography, and a systematic review published work on a stent for managing BPH. OBJECTIVES To validate the International Consultation on Incontinence Nocturia Quality‐of‐life (NQoL) questionnaire in Italian (IT‐NQoL) and use it to evaluate the impact of surgical treatment on nocturia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…In one study conducted in 547 men, nocturia was found to be signifi cantly associated with depressive symptoms, and it was suggested that nocturia may be predictive of depression [ 27 ] . Another study reported a signifi cant correlation between the severity of nocturia and poor sleep quality, and found that sleep quality was improved after surgical intervention [ 28 ] . Although a close association exists between depressive symptoms, poor sleep quality and nocturia, no causal relationship has been established.…”
Section: Discussionmentioning
confidence: 99%
“…In one study conducted in 547 men, nocturia was found to be signifi cantly associated with depressive symptoms, and it was suggested that nocturia may be predictive of depression [ 27 ] . Another study reported a signifi cant correlation between the severity of nocturia and poor sleep quality, and found that sleep quality was improved after surgical intervention [ 28 ] . Although a close association exists between depressive symptoms, poor sleep quality and nocturia, no causal relationship has been established.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Further, survey studies have shown that the greater the number of nocturnal voids, the greater the self-described poor sleep, insomnia symptoms, and daytime sleepiness. [7][8][9][10][11][12][13][14][15] For those individuals who report nocturia as bothersome there is even a stronger correlation with disturbed sleep. 13,16 As noted, to date, no study of the relationship between sleep and nocturia has used objective measurements of sleep, nor have previous studies examined the relationship between sleep and nocturia prospectively, on a night-to-night basis.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…The proper assessment of nocturia in patients with LUTS was traditionally difficult to define because most questionnaires included nocturia among other LUTS and added them together to form a score (eg, International Prostate Symptom Score [IPSS]/American Urologic Association Symptom Score, Benign Prostatic Hyperplasia Impact Index, Danish Prostatic Symptom Score) [36]. Very few instruments examine the impact of nocturia alone on QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The 12 items pertaining to nocturia are scored from 0 (no symptoms) to 4 (symptoms always present). The 13th item related to QoL is scored from 0 (no symptoms) to 10 (severe nocturia impact on QoL) [36,41]. The questionnaire takes approximately 5 min to fill out, and scores range from 0 to 48 [41].…”
Section: Discussionmentioning
confidence: 99%